Effects of Cross-Border Engineer Exchange on Innovation: Firm-Level Evidence from Hanoi in Vietnam and Calabarzon in the Philippines - Machikita, Tomohiro; Chi Binh, Truong Thi; Ueki, Yasushi (México y la Cuenca del Pacífico, 2015)
Using data from a survey to manufacturing firms, this paper attempts to detect sources of new technologies transferred to a well-established industrial district in Calabarzon, the Philippines, and a rapidly growing agglomeration in Hanoi, Vietnam. We find significant effects of exchange of engineers with customer or supplier on improvements in fundamental processes by firms in Hanoi. On the other hand, exchange of engineers significantly affects improvements in production and quality control of products newly introduced by firms in Calabarzon. The difference in the effects of exchanging engineers between the two industrial districts indicates difference in the stages of industrial development. Resumen: Utilizando los resultados de una encuesta aplicada a firmas manufactureras, en este artículo se busca identificar las fuentes de la transferencia tecnoló- gica en un distrito industrial consolidado en Calabarzón, en Filipinas, y en una aglomeración de rápido crecimiento en Hanoi, Vietnam. Encontramos efectos significativos por medio del intercambio de ingenieros entre empresas clientes y proveedoras, en la mejora de procesos fundamentales en las firmas en Hanoi. Por otro lado, el intercambio de ingenieros afecta de manera significativa para lograr mejoras en la producción y en el control de calidad de productos nuevos introducidos por las firmas en Calabarzón. La diferencia de los efectos del intercambio de ingenieros entre los dos distritos industriales indica la diferencia en los grados relativos de desarrollo industrial.